Digital Transformation of Public Service Malls: Enhancing Efficiency and Accessibility in the Digital Era - Dwi Hartutik; V. Rudy Handoko; Teguh Priyo Sadono (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study explores the digital transformation of the Public Service Mall (PSM) in Indonesia, emphasizing its role in enhancing bureaucratic efficiency, accessibility, and public satisfaction. Employing a qualitative library research approach, the analysis synthesizes existing literature, policy documents, and case studies to comprehensively understand the concepts, strategies, and challenges associated with digitalization in public services. The findings highlight that digital transformation, particularly through integrated and user-friendly online platforms, significantly reduces procedural complexity, shortens service delivery times, and broadens access for remote and underserved communities. Key supporting technologies such as cloud computing, artificial intelligence, and robust data security are vital for effective implementation, while strong policy frameworks and inter-agency collaboration underpin sustainable development. Despite notable progress, challenges including infrastructural limitations, human resource capacity, resistance to change, and regulatory barriers must be addressed through targeted investments, capacity building, and regulatory harmonization. The study concludes that a holistic and adaptive approach, coupled with ongoing research into social impacts and regional best practices, is essential to realize the full potential of digital public services and foster inclusive, efficient, and transparent governance in the digital era.